PENGARUH SELF-EFFICACY DAN SOCIAL SUPPORT TERHADAP ACADEMIC STRESS PADA MAHASISWA DI KOTA PADANG - Hidayati, Miskatul; Juwita, Silvi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Academic stress is a common problem experienced by college students due to their inability to cope with and manage academic demands. This study aims to determine the influence of self-efficacy and social support on academic stress among college students in Padang. The study employed a quantitative correlational approach involving 385 students selected using accidental sampling. Data were collected using the Academic Stress Scale, the General Self-Efficacy Scale, and the Social Support Scale, all of which met validity and reliability criteria. Data analysis was conducted using multiple linear regression. The results indicate that self-efficacy has a negative and significant effect on academic stress (p<0.05), whereas social support does not have a significant effect on academic stress (p>0.05). Simultaneously, self-efficacy and social support contributed 3.5% to academic stress, while the remaining 96.5% was influenced by other factors outside the scope of this study. These findings indicate that self-efficacy plays a role in reducing academic stress among students.